Penerapan Sistem Pertanian Organik dengan Aplikasi Pupuk Organik Cair Urin Kelinci pada Padi Sawah - Yugi Rahayu Ahadiyat; Ida Widiyawati; Ahmad Fauzi (Institut Pertanian Bogor, 2021)
The Ngudi Tani farmer group is one of the farmer groups in Bobosan Village, North Purwokerto District, Banyumas Regency. The rice fields in the Bobosan village area have irrigation system and the water is always available throughout the year, however rice farming has not been applied environmentally friendly agricultural system yet. Liquid Organic Fertilizer (LOF) of urine rabbit with quince bengal fruit could apply as substitution of fertilizer and pesticide synthetics.The purpose of this service activity was to increase understanding and knowledge about organic farming systems with the application of LOF in lowland rice and how to make rabbit urine LOF. Methods of activities were carried out through counseling and training related to LOF application in rice fields and makes use of rabbit urine LOF. The rice field plot was focused on the appropriate way of working and techniques in supporting rice production through the application of rabbit urine LOF. Counseling, training, demonstration plots and rabbit livestock introduction is successful even though not to all members of the farmer groups. The knowledge and skills of farmers have increased regarding rabbit livestock and processing of urine into liquid organic fertilizer and its application to lowland rice. The introduction of rabbit urine LOF in lowland rice cultivation has been responded positively by some members of farmer groups and farmers have understood the procedure for processing rabbit urine waste into liquid organic fertilizer and its application in rice plants.